2021
DOI: 10.3389/fimmu.2021.721970
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular CIRP Induces an Inflammatory Phenotype in Pulmonary Fibroblasts via TLR4

Abstract: Extracellular cold-inducible RNA-binding protein (eCIRP), a new damage-associated molecular pattern (DAMP), has been recently shown to play a critical role in promoting the development of bleomycin-induced pulmonary fibrosis. Although fibroblast activation is a critical component of the fibrotic process, the direct effects of eCIRP on fibroblasts have never been examined. We studied eCIRP’s role in the induction of inflammatory phenotype in pulmonary fibroblasts and its connection to bleomycin-induced pulmonar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 86 publications
0
11
0
Order By: Relevance
“…Hemorrhagic shock increases eCIRP levels and activates STING through the TLR4/MyD88/TRIF pathway to exacerbate inflammation ( 55 ). In lung fibroblasts, eCIRP amplifies pro-inflammatory cytokines in a TLR4-dependent manner, triggering pulmonary fibrosis ( 54 ). As a receptor for eCIRP, TREM-1 plays a vital role in ischemia-reperfusion in the liver, intestine, and other organs ( 60 ), and induces inflammation in macrophages and neutrophils ( 35 ), forming NETs ( 61 ).…”
Section: Role Of Ecirp In Inflammatory Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemorrhagic shock increases eCIRP levels and activates STING through the TLR4/MyD88/TRIF pathway to exacerbate inflammation ( 55 ). In lung fibroblasts, eCIRP amplifies pro-inflammatory cytokines in a TLR4-dependent manner, triggering pulmonary fibrosis ( 54 ). As a receptor for eCIRP, TREM-1 plays a vital role in ischemia-reperfusion in the liver, intestine, and other organs ( 60 ), and induces inflammation in macrophages and neutrophils ( 35 ), forming NETs ( 61 ).…”
Section: Role Of Ecirp In Inflammatory Diseasesmentioning
confidence: 99%
“…Pulmonary fibrosis is a devastating sequela of many chronic inflammatory diseases characterized by a progressive decline in lung volume capacity and high mortality. eCIRP induces pro-inflammatory cytokines and differentially-expressed pathways in lung fibroblasts in a TLR4-dependent manner, and the accessory pathways MD2 and Myd88 are involved in the induction of the inflammatory phenotype ( 54 ). Furthermore, CIRP is involved in the regulation of pulmonary fibrosis, as eCIRP can directly activate and induce inflammatory phenotype fibroblasts (IPF) in the lung.…”
Section: Role Of Ecirp In Inflammatory Diseasesmentioning
confidence: 99%
“…Toll-like receptor 4 (TLR4) signaling through Myd88-dependent IRAK-M expression has been shown to be increased in peripheral blood cells from idiopathic pulmonary fibrosis patients compared to controls and was linked to the alternative macrophage activation, profibrotic phenotype, and collagen production [ 66 , 67 ]. Further, it has also been reported that TLR signaling could trigger the pathology of pulmonary fibrosis by increasing the production and release of cytokines such as IL-6, TNF-α, and IL-1β [ 68 ]. In IPF, patients display higher levels of IL-6 in plasma and alternatively activated macrophages [ 31 , 69 , 70 ].…”
Section: Macrophages In Fibrosismentioning
confidence: 99%
“…Our lab has previously shown that eCIRP is a potent inducer of TNF-α, IL-1β, and IL-6 in macrophages in a TLR4 dependent manner, and that CIRP -/- mice have an ameliorated response to the acute injury brought on by the storm of these proinflammatory cytokines [ 13 , 15 , 18 , 59 ]. In our recently published observations, we have seen that eCIRP is a powerful inducer of these cytokines in pulmonary fibroblasts as well [ 60 ]. Therefore, we conjectured that eCIRP can promote the persistent autocrine/paracrine activation of fibroblasts by inducing the release of proinflammatory cytokines from macrophages and fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Since we have demonstrated that treatment with C23 attenuates inflammation and ameliorates clinically relevant endpoints in various animal models shown to be aggravated by eCIRP [ 28 , 30 , 70 ], we ventured to see if blocking eCIRP using C23 peptide on TLR4-MD2 complex can ameliorate the bleomycin-induced fibrotic response in the lung. We have already shown that the inflammatory pathways and cytokines are at their peak of expression on day 14 after the start of bleomycin injection and there is a drop in expression of these pathways and cytokines on day 21 [ 60 ]. This is in line with Raventti et al, who showed there is an increase in infiltration of total white blood cells, neutrophils, and macrophages in lung tissue at day 14 of bleomycin injection that decreases on day 21 [ 71 ].…”
Section: Discussionmentioning
confidence: 99%